Correlates of Television Advertisement Viewing Behaviour of Rural Viewers - Chaturvedi, Vinod Kumar; Singh, Premlata (Indian Journal of Extension Education, 2010)
The television (TV) as a medium of advertising has immense potential in urban as well rural India. The present study designed to throw light on TV advertisement viewing behaviour and reveal its association with selected socio-personal factors of rural viewers was undertaken. The advertisement viewing behaviour (de pendent variable) was operationalised in terms of two distinctive features namely 'extent of exposure' and 'extent of interest' of respondents in viewing TV advertisements. The study was conducted in two randomly selected villages of Kanjhawala block of Delhi. A total of 100 respondents (males) were included in the sample who owned as well as viewed TV for at least past six months. The study revealed that a majority of the respondents (62%) exhibited low level of TV advertisement viewing behaviour followed by 23 per cent under medium level and 15 per cent respondents falling under high level. The association between age and TV advertisement viewing behaviour was found to be negatively and significantly correlated at 0.05 level of probability. Education and attitude towards TV advertisements were positively and significantly correlated at 0.05 level and 0.01 level of probability respectively, with TV advertisement viewing behaviour. The corre lation coefficient (h) in respect of rest of the variables was found to be non-significant which indicated that they were not a deciding factor of TV advertisement viewing behaviour. The determinants of multiple regres sion (R2) indicated that all the independent variables under the study jointly explained only 40.4 per cent variation in TV advertisement viewing behaviour of rural viewers.